Nghiên cứu ảnh hưởng kép của clay và ion pha tạp tới khả năng ức chế quá trình ăn mòn thép CT3 của nanocompozit polypyrol/clay - Trung, Vũ Quốc; Thương, Nghiêm Thị; Hoan, Phạm Văn; Phùng, Dương Quang; Quế, Lê Xuân (Vietnam Journal of Chemistry, 2014)
In this paper, the nanocomposites of polypyrrole and clay were prepared by chemical polymerization. The polypyrole was doped by corrosion inhibiting molypdate anion. The nanocomposite powder was dispered in PVA matrixes in order to study the influences of both dopping anion and clay on corrosion of steel CT3. Results of the measurements of open circuit potential, polarization and electrochemical impedance spectroscopy showed that in the presence of clay and/or molipdate anion the coatings containing polypyrrole obviously improved the corrosion protection for steel in comparison with the cases of that consisting no dopping anion and/or no clay.